Sociomedical Survey of People with Mental Illness in Andhra Pradesh’s Anantapuramu District: Exploring the Sociomedical Landscape of Mental Illness in Andhra Pradesh’s Anantapuramu District (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The entire well-being of people throughout civilizations depends on mental health. For the health standards of all human beings physical, mental and social aspects are critical and are interlinked and highly interconnected. Without sufficient support for mentally sick and promoting healthy mental health, no programme can be deemed complete. Mental diseases are commonly known to contribute significantly to the worldwide burden of illness. In every social and religious culture over the years there has persisted a continuous unfavorable attitude and a social refusal of those with mental illness. Mental disease is misunderstood by the general population of all the health conditions. The efficacy of patient treatment and rehabilitation are threatened by such low information and bad attitudes regarding mental illness. No single group preserves mental problems, they are actually universal. The important and critical component of health is mental health. The preamble of the World Health Organization says that health is a full condition of physical, mental or social well-being and not only a lack of illness and illness.